FDEM numerical study of the influence law of geostress on state and pressure of tunnel surrounding rock - Hu, Bo; Xiao, Mingqing; Fu, Xiaodong; Yang, Jian; Xu, Chen; Wu, Jiaming; Zhou, Yongqiang (Frontiers in Ecology and Evolution, 2023)
Surrounding rock pressure is a crucial parameter in tunnel engineering design, and its calculation is a classic challenge. The surrounding rock pressure is influenced by geostress, but existing calculation methods often do not take into account the effect of geostress. In this paper, finite discrete element method (FDEM) is used to study the design values of tunnel surrounding rock pressure under different geostress fields. Firstly, a set of calibration methods for input parameters of FDEM is summarized based on previous studies. Then, taking a high-speed railway tunnel in Ⅳ-level surrounding rock as an example, the excavation-induced failure process of the tunnel under the influence of gravity stress field and geostress field is simulated using the FDEM.By comparing the results with those of the finite element method simulation, the rationality of applying FDEM to the simulation of tunnel excavation is demonstrated. Next, a calculation method of surrounding rock pressure design value based on FDEM is proposed by introducing tunnel displacement criterion, and its validity is verified by comparing with the results of the theoretical formula. Finally, the surrounding rock pressure design values under different geostress are analyzed by using this calculation method. The results show that there are significant differences between the gravity stress field and the geostress field in the maximum principal stress distribution, failure zone form and crack distribution. The geostress directly influences the design value of surrounding rock pressure. As the geostress varies from 4MPa to 12MPa, the corresponding design value increases from 49KPa to 1288KPa, illustrating a quadratic relationship between them. With the corresponding design support force, the displacement of the surrounding rock is controlled within a reasonable range, ensuring the stability of the tunnel is maintained.